2014
DOI: 10.1021/ja506820r
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Correlated Dynamics in Intrinsically Disordered Proteins

Abstract: Intrinsically disordered proteins (IDPs) are involved in a wide variety of physiological and pathological processes and are best described by ensembles of rapidly interconverting conformers. Using fast field cycling relaxation measurements we here show that the IDP α-synuclein as well as a variety of other IDPs undergoes slow reorientations at time scales comparable to folded proteins. The slow motions are not perturbed by mutations in α-synuclein, which are related to genetic forms of Parkinson's disease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 66 publications
6
91
0
Order By: Relevance
“…Rotational diffusion of the polypeptide chain makes dynamics unobservable via dipolar, chemical shift anisotropy, or quadrupolar relaxation on timescales longer than the rotational time (69). Recently, Parigi et al (70) have shown by 1 H T 1 relaxation dispersion that a number of IDPs exhibit long-range rotational correlation times in the one-digit nanosecond range, which are comparable to folded proteins of similar size. For urea-denatured ubiquitin, 15 N relaxation data (71) indicate an isotropic reorientation of the N-H vectors, which is considerably faster than the rotational correlation time of 4 ns for folded ubiquitin (72).…”
Section: Discussionmentioning
confidence: 99%
“…Rotational diffusion of the polypeptide chain makes dynamics unobservable via dipolar, chemical shift anisotropy, or quadrupolar relaxation on timescales longer than the rotational time (69). Recently, Parigi et al (70) have shown by 1 H T 1 relaxation dispersion that a number of IDPs exhibit long-range rotational correlation times in the one-digit nanosecond range, which are comparable to folded proteins of similar size. For urea-denatured ubiquitin, 15 N relaxation data (71) indicate an isotropic reorientation of the N-H vectors, which is considerably faster than the rotational correlation time of 4 ns for folded ubiquitin (72).…”
Section: Discussionmentioning
confidence: 99%
“…as it was done for the experimental data [3] (the fit was in all cases very good, with a reduced χ 2 of about 10…”
Section: Simulated Proton Relaxometry Profilesmentioning
confidence: 64%
“…The first 2-µs of the H-H ACFs were taken for Fourier transformation, as a result, spectral densities from 0 to 50 GHz at 0.5 MHz intervals were obtained. R 1 of all non-exchangeable CH 3 , CH 2 and CH α protons were then calculated from the spectral densities, J(ω), through the equation , (eq. S3)…”
Section: Simulated Proton Relaxometry Profilesmentioning
confidence: 99%
See 2 more Smart Citations